(untitled) (Journal of the Bangladesh Agricultural University, 2013)
The study was conducted in three mungbean growing districts namely Barisal, Patuakhali and Noakhali of Bangladesh during the period of 2010-11 to assess the extent of technology adoption, profitability, farmers attitude, and constraints to mungbean. The study focuses the level of technology adoption for both input use and agronomic practices follow by most of the farmers were close to the recommendation which was very encouraging. All the farmers adopted improved mungben varieties and they were mostly influenced by DAE personnel and neighboring farmers. The yield of improved mungbean was found 824 kg/ha, which was more or less same with the national average of 820 kg/ha. The cultivation of improved mungbean was profitable since the net profit and BCR were Tk.38850 and 1.62 respectively. The variables such as experience, training, organizational membership, relation with different media, and mungbean suitable area had positive and significant influence in increasing the area under mungbean cultivation. Maximum number of farmers showed positive attitude towards improved mungbean cultivation of which 67% farmers wanted to increase its cultivation in the next year. The major constraints to improved mungbean production were; high price of insecticides, lack of labour and disease and insect infestation. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14920 J. Bangladesh Agril. Univ. 10(2): 283-289, 2012